High conopeptide diversity in Conus striatus: Revealed by integration of two transcriptome sequencing platforms - Liao, Yanling; Peng, Chao; Zhu, Yabing; Fu, Jinxing; Ruan, Zhiqiang; Shi, Qiong; Gao, Bingmiao (Frontiers in Marine Science, 2022)
Marine cone snail venoms represent a vast library of bioactive peptides with proven potential as research tools, drug leads, and therapeutics. In this study, a transcriptome library of four different organs, namely radular sheath, venom duct, venom gland, and salivary gland, from piscivorous Conus striatus was constructed and sequenced using both Illumina next-generation sequencing (NGS) and PacBio third-generation sequencing (TGS) technologies. A total of 428 conotoxin precursor peptides were retrieved from these transcriptome data, of which 413 conotoxin sequences assigned to 13 gene superfamilies, and 15 conotoxin sequences were classified as unassigned families. It is worth noting that there were significant differences in the diversity of conotoxins identified from the NGS and TGS data: 82 conotoxins were identified from the NGS datasets while 366 conotoxins from the TGS datasets. Interestingly, we found point mutations in the signal peptide sequences of some conotoxins with the same mature sequence. Therefore, TGS broke the traditional view of the conservation of conotoxin signal peptides and the variability of mature peptides obtained by NGS technology. These results shed light on the integrated NGS and TGS technologies to mine diverse conotoxins in Conus species, which will greatly contribute to the discovery of novel conotoxins and the development of new marine drugs.